2013
DOI: 10.1080/01635581.2013.767366
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Heat Shock Proteins by Phenethyl Isothiocyanate Results in Cell-Cycle Arrest and Apoptosis of Human Breast Cancer Cells

Abstract: Heat shock proteins (HSPs) are chaperones for several client proteins involved in transcriptional regulation, signal transduction, and cell cycle control. HSPs (27, 70, and 90) are abundantly expressed in a wide range of cancers and are transcriptionally regulated by heat shock factor (HSF1). Most of the synthetic HSP inhibitors exhibit toxicity, therefore, searching for inhibitors with limited or no toxicity will be of help. The objective of the present study was to determine the effect of natural isothiocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…PEITC is a potential cancer chemopreventive constituent of edible cruciferous vegetables and has been shown to inhibit various models of cancer, including prostate, breast, ovarian, oral and lung cancer (3)(4)(5)(6)(7). The present study aimed to characterize the anti-leukemia effects of PEITC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEITC is a potential cancer chemopreventive constituent of edible cruciferous vegetables and has been shown to inhibit various models of cancer, including prostate, breast, ovarian, oral and lung cancer (3)(4)(5)(6)(7). The present study aimed to characterize the anti-leukemia effects of PEITC.…”
Section: Discussionmentioning
confidence: 99%
“…Phenethyl isothiocyanate (PEITC) is an important compound obtained from cruciferous vegetables that is effective in numerous types of cancer, including prostate, breast, ovarian, oral and lung cancer (3)(4)(5)(6)(7). Several mechanisms, including the inhibition of cytochrome p450 enzymes, the induction of phase II detoxification enzymes (8) and the activation of death receptors 4 and 5 (9), are involved in the anti-tumor effects of PEITC.…”
Section: Introductionmentioning
confidence: 99%
“…These effects were accompanied by cell-cycle arrest at G2/M phase and apoptosis by activation of caspases 3 and 9. 35 The chemopreventive activity of blueberries was studied by Yee et al 22 in triple-negative breast cancer cell lines. It was revealed that the phytochemicals present in blueberries decreased proliferation of HCC38, HCC1937, and MDA-MB-231 cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Boesenbergin A treatment is caused significantly suppressing of HSP70 in human T4-lymphoblastoid cells [36]. Phenethyl isothiocyanate (PEITC), a natural compound found in some plants, significantly reduced HSP27, HSP70, HSP90 and HSF-1 expressions in MCF-7 and MDA-MB-231 breast cancer cell lines [134]. Triptolide from Triptergium wilfordii suppressed HSP70 expression via inhibiting heat shock response in HeLa cells [141].…”
Section: Plant-based Hsp Inhibitionsmentioning
confidence: 99%